Peran Pendidikan Islam dalam Mencegah Perilaku Intoleransi Kalangan Remaja di MTs PAB 5 Klambir Lima - Ridhayani Lestari; Kamil Kamil; Charles Rangkuti (Medan Resource Center, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) in preventing intolerant behavior among adolescents at MTS PAB 5 Klambir Lima. The phenomenon of intoleranceposes significant challenges to students’ character development. Although numerous studies have discussed character education and religious instruction, limited research specifically examines how PAI is operationalized at the madrasah level to address everyday manifestations of intolerance. This gap underscores the need for context-based qualitative inquiry into the practical strategies employed by PAI teachers. This research employed a descriptive qualitative method. Data were collected through observation, in-depth interviews, and documentation involving 12 informants, consisting of the principal, three PAI teachers, and eight students. The findings indicate that PAI teachers play a central role in instilling tolerance values through three primary approaches: integrative and contextual learning, role modeling, and the internalization of Islamic socio-religious values. Teachers consistently emphasize respect for differences in belief, while fostering polite, courteous, and respectful behavior in daily interactions. Several obstacles were identified, predominantly psychological and social factors such as limited emotional control and peer influence. However, these challenges are addressed through continuous character guidance and reflective religious activities. Overall, the findings show indications of effectiveness within the context of this study in shaping adolescents who demonstrate moderate attitudes, noble character, and readiness to live harmoniously in a diverse society. This study contributes to the development of Islamic education discourse by providing empirical insights into practical strategies for strengthening tolerance-based character education at the madrasah level.